SOCIAL STUDIES: ANALISIS INTEGRASI KOMPETENSI TRANSFORMATIF OECD 2030 DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL DI SEKOLAH DASAR - Rif’an Fazrin Zulfikar; Sizka Amelia Febrianti; Aliya Putri Gunawani; Yona Wahyuningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the integration of OECD 2030 Transformative Competencies in social studies learning in elementary schools to develop active, globally competitive, and adaptive students. These Transformative Competencies are considered relevant to the demands of the 21st century, which emphasize critical, creative, and collaborative thinking skills. This study uses a Systematic Literature Review (SRL) research design by reviewing 30 published literatures from 2019-2025, both from national and international sources, discussing the implementation of 21st-century and social studies learning reform. The results of the study indicate that the integration of Transformative Competencies has been implemented into the Independent Curriculum and the strengthening of the Pancasila Student Profile, which emphasizes student-centered learning and the implementation of the Anticipation-Action-Reflection (A-A-R) learning cycle. This transformation shifts the paradigm of social studies learning from its original focus on conventional memorization patterns to contextual, collaborative, and holistic issue-based learning. Thus, the integration of Transformative Competence in social studies learning enriches 21st-century competencies and strengthens students' character and social responsibility.